Fit for purpose - Auld, Sharon M (PINS-Psychology in Society, 2015)
Smith, Cora, Lobban, Glenys & O’Loughlin, Michael (eds) (2013) Psychodynamic psychotherapy in South Africa. Johannesburg: Wits University Press. ISBN 978-1-86814-603-1 pbk. Pages xi + 292